OECD Project "The role of qualifications systems in promoting lifelong learning" : country background report: Germany - Reuling, Jochen [Verfasser]; Hanf, Georg [Verfasser] (Bertelsmann, 2004)
"The national Country Report is part of an OECD Project of the same name. Country reports were produced by the member states participating in the project on how the national qualifications systems influence the patterns and the quality of lifelong learning and what actions have been taken to promote lifelong learning. In the first part of the report the most important qualifications subsystems in Germany after upper secondary education are described. Then, on the basis of available research findings, the influence of qualifications systems on learning is analysed. This is followed by documentation and analysis of the principal reforms in the vocational qualifications subsystems in the past few years and their effects on mechanisms that may be of importance for lifelong learning. Finally, with the help of examples, the connection between qualifications systems and learning at the level of providers and users of teaching and learning programmes is examined." (BIBB)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; G 1.2.3 Qualifikationsentwicklungen; Qualifikationserwerb; Lebenslanges Lernen; OECD; Bundesrepublik Deutschland